Free love - Hadley, Tessa 1956- (Jonathan Cape, 2022)
"1967. While London comes alive with the new youth revolution, the suburban Fischer family seems to belong to an older world of conventional stability: pretty, dutiful homemaker Phyllis is married to Roger, a devoted father with a career in the Foreign Office. Their children are Colette, a bookish teenager, and Hugh, the golden boy. But when the twenty-something son of an old friend pays the Fischers a visit one hot summer evening, and kisses Phyllis in the dark garden after dinner, something in her catches fire. Newly awake to the world, Phyllis makes a choice that defies all expectations of her as a wife and a mother. Nothing in these ordinary lives is so ordinary after all, it turns out, as the family's upheaval mirrors the dramatic transformation of the society around them. With scalpel-sharp insight, Tessa Hadley explores her characters' inner worlds, laying bare their fears and longings. Daring and sensual, Free Love is a compelling, irresistible exploration of romantic love, sexual freedom, and our hunger for more truth and meaning in our lives."
Keywords: Fiktionale Darstellung